2020
DOI: 10.31937/akuntansi.v12i2.1702
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corporate Governance, Firm Size, Profitability, and Growth Opportunities on the Value Relevance of Accounting Earnings – A Study of the Indonesia Stock Exchange

Abstract: Capital market serves as an alternative financing-wise and as a means investment-wise. Relevance of accounting information comes out as profound to investors as can be observed within the financial statements of a company. The aim of this study was to figure out the effects of corporate governance, firm size, profitability, and growth opportunities on the value relevance of accounting earnings. The present research used a quantitative method and secondary data in the form of annual reports, and the objects hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Large companies have a lot of assets, hence their asset to liability ratio will be high. Previous research has shown that there is a link between the size of a company and its stock price (Odoemelam et al, 2019;Putri & Panggabean, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Large companies have a lot of assets, hence their asset to liability ratio will be high. Previous research has shown that there is a link between the size of a company and its stock price (Odoemelam et al, 2019;Putri & Panggabean, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The prospect of the company's future growth is explained by growth opportunities. The bigger the company's potential for growth, the greater the company's ability to make earnings in the future (Putri & Panggabean, 2020). This will undoubtedly have an impact on the value relevance of accounting earnings.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Peluang pertumbuhan dijadikan sebagai penentu prospek perusahaan dalam perkembangannya sehingga perusahaan membutuhkan dana yang besar dari hasil investasi pemegang saham untuk mendanai operasionalnya (Putri & Panggabean, 2020). Peluang pertumbuhan perusahaan dibuktikan memiliki hubungan positif terhadap manajemen laba berdasarkan penelitian Debnath (2017) dan Fung & Goodwin (2013).…”
Section: Peluang Pertumbuhan Perusahaan Terhadap Manajemen Labaunclassified